Genetic and epigenetic susceptibility of airway inflammation to PM2.5 in school children: new insights from quantile regression - Yue Zhang; Muhammad T. Salam; Kiros Berhane; Sandrah P. Eckel; Edward B. Rappaport; William S. Linn; Rima Habre; Theresa M. Bastain; Frank D. Gilliland (BMC, 2017)
Abstract Background The fractional concentration of exhaled nitric oxide (FeNO) is a biomarker of airway inflammation that has proved to be useful in investigations of genetic and epigenetic airway susceptibility to ambient air pollutants. For example, susceptibility to airway inflammation from exposure to particulate matter with aerodynamic diameter < =2.5 μm (PM2.5) varies by haplotypes and promoter region methylation in inducible nitric oxide synthase (iNOS encoded by NOS2). We hypothesized that PM2.5 susceptibility associated with these epigenetic and genetic variants may be greater in children with high FeNO from inflamed airways. In this study, we investigated genetic and epigenetic susceptibility to airborne particulate matter by examining whether the joint effects of PM2.5, NOS2 haplotypes and iNOS promoter methylation significantly vary across the distribution of FeNO in school children. Methods The study included 940 school children in the southern California Children's Health Study who provided concurrent buccal samples and FeNO measurements. We used quantile regression to examine susceptibility by estimating the quantile-specific joint effects of PM2.5, NOS2 haplotype and methylation on FeNO. Results We discovered striking differences in susceptibility to PM2.5 in school children. The joint effects of short-term PM2.5 exposure, NOS2 haplotypes and methylation across the FeNO distribution were significantly larger in the upper tail of the FeNO distribution, with little association in its lower tail, especially among children with asthma and Hispanic white children. Conclusion School-aged children with higher FeNO have greater genetic and epigenetic susceptibility to PM2.5, highlighting the importance of investigating effects across the entire distribution of FeNO.